Mango (Mangifera indica) Jam Production Technology - Mandey, Lucia C.; Mamuaja, Christine F. (Pascasarjana Unsrat, 2016)
Mango fuit jam is a semi-wet food products made of mango pulp processing and sucrose with or without the addition of permitted food additives. Mango fruit as other horticultural products is a food that can be easily damaged or rotten. In the harvest season mango production is very plentiful and many are not consumed, as a result, mango fruit becomes spoiled. The total spoiled mangoes can reach 35%, due to the perishable nature of this fruit cause losses to farmers and fruit sellers. The greatest losses occur during the harvest because of various factors, among others that have not been done are limited usage just as fresh fruit comsumption and limited method of processing and preservation. The purposes of this study were to examine some characteristic quality of mango jam with parameters of pH, water content, total sugar, total dissolved solids, organoleptic test and spreading ability with addition of different sucroses. The expected benefits of this research were providing information about mango jam production technology-model as other method to diversify the usage of mango as processed food products. This study used a completely randomized design (CRD) arranged in factorial, with two factors and three replications. A factor was the type of mango with two levels, namely A1 = dodol mango and A2 = kweni mango; B factor was the concentration of sucrose, in which B1 = 30% sucrose, B2 = 40% sucrose, and B3 = 50% sucrose, with the measured parameters were pH, water content, total sugar, total dissolved solids, organoleptic test, color, taste, smell, and preading ability. The results of this study showed that mango jam (dodol mango and kweni mango) with the 50% sucrose addition on dodol mango and kweni mango with all observed parameters produced qualified jam with the quality set by the Indonesian National Standard. Keywords: quality of mango jam, sucrose